Dynamics of Supporters and Inhibitors of Social Emotional Learning (SEL) Implementation by Teachers in Learning at SDN Rajek - Haryanto, Haryanto; Murniati, Ngurah Ayu Nyoman; Supandi, Supandi (FKIP - Universitas Riau, 2026)
This research was motivated by an anomaly in the Education Report Card data at SDN Rajek, where the increase in teacher well-being (79.00) was not linear with the low level of student well-being (66.30). This phenomenon indicates a barrier to the transmission of positive emotions within the school climate. This research aims to formulate a solution model to convert teacher well-being into Social Emotional Competence (SEC), which impacts students. Using a qualitative case study method, data was collected through interviews, observations, and document review. The results introduce the